2012
DOI: 10.1002/chem.201202140
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Amination of Aryl Chlorides with a Monoligated Palladium Catalyst: Kinetic Evidence for a Cooperative Mechanism

Abstract: Combined spectroscopic, crystallographic, and kinetic studies of the mechanism of aromatic amination with the efficient dinuclear Pd precatalyst [Pd(2)Cl(μ-Cl)PtBu(2)(Bph-Me)] (Bph-Me = 2'-methyl-[1,1'-biphenyl]-2-yl) have revealed overlapping, yet cooperative, mechanistic scenarios, the relative weights of which are strongly influenced by the products formed as the reaction proceeds. The stability and evolution of the precatalyst in solution has been studied and several metalation pathways that point to a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…In the same way that Pd­(I) dimeric precatalysts can be activated by disproportionation to Pd(0) and Pd­(II) species, experimental conditions promoting the reverse reaction can deactivate Pd­(II) precatalysts. This may occur when precatalyst activation by formal reduction of Pd­(II) to Pd(0) is not fast enough as to avoid their coexistence in the reacting solution (Figures and ) or with substrates undergoing slow oxidative addition in the presence of large catalyst loadings.…”
Section: Catalyst Deactivation By Formation Of Palladium(i) Dimersmentioning
confidence: 99%
“…In the same way that Pd­(I) dimeric precatalysts can be activated by disproportionation to Pd(0) and Pd­(II) species, experimental conditions promoting the reverse reaction can deactivate Pd­(II) precatalysts. This may occur when precatalyst activation by formal reduction of Pd­(II) to Pd(0) is not fast enough as to avoid their coexistence in the reacting solution (Figures and ) or with substrates undergoing slow oxidative addition in the presence of large catalyst loadings.…”
Section: Catalyst Deactivation By Formation Of Palladium(i) Dimersmentioning
confidence: 99%
“…2À that are known to be catalytically active (Bouquillion et al, 1999;Jimeno et al, 2012;Lassahn et al, 2003;Mu et al, 2012), by using [PdCl 4 ] 2À in the form of its sodium salt as a typical precursor in aqueous palladium(II) chemistry.…”
Section: Chemical Contextmentioning
confidence: 99%
“…4 The synthesis of the reported seven-membered palladacycles comprises (1) insertion of alkynes into the Pd−C bond of five-membered palladacycles 5 or of RNC into the Pd−C bond of six-membered palladacycles, 6 (2) coordination of a donor atom of a functionalized ligand previously C-bonded to Pd(II), 7 (3) coordination to Pd(II) of bis-N-heterocyclic carbenes, bisylides, or phosphine-carbene ligands usually generated in situ, 8 (4) oxidative addition of Ar P,N,S X (Ar P,N,S = PR 2 , NR 2 , py, or RS-functionalized aryl; X = Br, I) to Pd(0) compounds, 9 followed occasionally by a C−C coupling reaction, 10 and (5) C−H activation by a Pd(II) salt, where the metalated CH can belong to an allyl, 11 a phenyl, 4 or a methyl group. 12 It is worthy to note that the latter are very uncommon processes: the allylic activation affords a pincer complex, 11 the C aryl −H activation occurs in a tetraphenylcyclobutadiene complex of Co(II), 4 and the C(sp 3 )−H palladation takes place in a di-tert-butyl(biaryl)phosphine coordinated to Pd(II). 12 Shi, Zhao, et al have also reported the sequential alkenylation of oxalyl amide protected phenylpropylamine derivatives via a seven-membered palladacycle, which can be detected in a stoichiometric reaction in an NMR tube.…”
Section: ■ Introductionmentioning
confidence: 99%
“…12 It is worthy to note that the latter are very uncommon processes: the allylic activation affords a pincer complex, 11 the C aryl −H activation occurs in a tetraphenylcyclobutadiene complex of Co(II), 4 and the C(sp 3 )−H palladation takes place in a di-tert-butyl(biaryl)phosphine coordinated to Pd(II). 12 Shi, Zhao, et al have also reported the sequential alkenylation of oxalyl amide protected phenylpropylamine derivatives via a seven-membered palladacycle, which can be detected in a stoichiometric reaction in an NMR tube. 13 The initial work of Cope and Friedrich 14 on cyclopalladation of arylalkylamines stated that this type of ligand could be orthometalated only when (1) the amine was tertiary, (2) a five-membered metallacycle was formed, and (3) the aromatic ring was not deactivated toward electrophilic attack.…”
Section: ■ Introductionmentioning
confidence: 99%